1985
DOI: 10.1111/j.1525-1594.1985.tb04400.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Monitoring of Plasma Exchange in Primary IgA Nephropathy

Abstract: Plasma exchange (PE) has recently been proposed for primary immunoglobulin (Ig)-A nephropathy (PIgAGN) with progressive course. To develop suitable guidelines for PE in these cases, the authors evaluated the clinical usefulness of some immunological parameters in five patients with PIgAGN treated with PE combined with immunosuppressive drugs and small doses of corticosteroids. These parameters included the levels of IgA-containing immune complexes (IgAIC) by a specific conglutinin assay, the function of the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Complement is a crucial mediator of renal injury in experimental models of IgAN [41], and signs of alternative complement pathway activation have been demonstrated in patients with IgAN and Henoch-Schönlein purpura nephritis [42]. The process has been considered to be antigen mediated [43].…”
Section: Modulation Of MC Functions By Aberrantly Glycosylated Iga Anmentioning
confidence: 99%
“…Complement is a crucial mediator of renal injury in experimental models of IgAN [41], and signs of alternative complement pathway activation have been demonstrated in patients with IgAN and Henoch-Schönlein purpura nephritis [42]. The process has been considered to be antigen mediated [43].…”
Section: Modulation Of MC Functions By Aberrantly Glycosylated Iga Anmentioning
confidence: 99%
“…In previous studies conducted at our institution we detected increased levels of complement-fixing KIgAIC in patients with active IgAN, with the levels of KIgAIC being significantly correlated with C3d levels [18]. Of interest, in a study of patients with progressive IgAN treated with plasma exchange, the clinical benefits corresponded with a decrease in KIgAIC and complement breakdown products [19].…”
Section: Complement Activation In Iga Nephropathymentioning
confidence: 80%
“…Case reports and case series from previous decades have addressed the PE treatment of IgAN patients with rapidly progressive kidney failure and crescent formation on renal biopsy (online suppl. table S2) [9][10][11][12][13][17][18][19][20][21] . Coppo et al [9] studied the effects of PE in 5 patients with progressive IgAN and found that PE delayed disease progression in the 3 patients with crescent formation, but did not delay progression in the patients with advanced sclerotic lesions [13] .…”
Section: Discussionmentioning
confidence: 99%
“…table S2) [9][10][11][12][13][17][18][19][20][21] . Coppo et al [9] studied the effects of PE in 5 patients with progressive IgAN and found that PE delayed disease progression in the 3 patients with crescent formation, but did not delay progression in the patients with advanced sclerotic lesions [13] . In another 2 reports, PE treatment successfully restored kidney function in a child with CreIgAN and rapid renal function deterioration despite intravenous methylprednisolone therapy [10,22] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation